Menneskelige(re) møter om samhandling, fellesskap og empati mellom beboere i en skjermet avdeling på sykehjem - Hillestad, Adelheid Hummelvoll (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"Humanizing Encounters is about the sense of community that exists between persons with dementia. This book is the outcome of a year of ethnographic fieldwork at the specialized dementia care units of two different long-term nursing facilities. Through participatory observation in these units, the author discerned the various ways residents interacted, collaborated and expressed care for each other. The potential for fellowship among residents of dementia care facilities is explored primarily through fieldwork, phenomenological perspectives and spatial theory. It suggests that persons with dementia experience a greater sense of community than previous research has recognized. Thus the book contributes to a widening of the relational focus in individually oriented caregiving practices to also include collaboration and relations between groups of people with dementia. Humanizing Encounters is a contribution to our evolving understanding of the development of community within the dementia care units of skilled nursing homes. It will be relevant to all those who work with and on behalf of people with dementia, as well as those with an interest in this area from a humanistic perspective."